The association between exposure to community violence and somatic symptoms through bullying victimization among African American adolescents in Chicago: A developmental trauma approach. Issue 5 (17th January 2023) - Lawrence, Timothy I.; Hong, Jun S.; Sopchak, Kelly S.; Voisin, Dexter R.
Abstract: Background: The developmental trauma theory suggests that traumatic events impede the ability of individuals to form interpersonal relationships, impair cognition, affect, and increase the vulnerability of adolescents to develop psychopathology. However, few studies have examined the applicability of this theory among African American adolescents who were exposed to community violence and adverse outcomes, including bullying victimization and somatic symptoms. Aims: Therefore, the purpose of the present study is to first test the association between exposure to community violence and somatic symptoms. Then, we explored whether bullying victimization mediated the relationship between exposure to community violence and somatic symptoms while controlling for gender differences and substance use ( n  = 622). Results: Results suggest that exposure to community violence is positively associated with somatic symptoms. Moreover, the association between exposure to community violence and somatic symptoms was mediated by bullying victimization. Discussion and Conclusion: These results were consistent with the developmental trauma theory, such that trauma could increase the vulnerability for future victimization, thus, leading to somatic symptoms. Implications for research and practice are discussed.